Curriculum Management in Islamic Boarding Schools: Integrating Islamic Values and Global Needs - Dace; Setia Budi (Edukasiana: Journal of Islamic Education, 2025)
The management of the curriculum in pesantren plays a crucial role in aligning Islamic values with the demands of globalization. As an Islamic educational institution, pesantren need to adapt their curriculum to remain relevant to the times, while preserving the traditions that have been passed down. This study aims to examine how pesantren design, manage, and develop curricula that integrate religious education with 21st-century skills. The approach used in this research is qualitative, through literature studies and observations of several pesantren that have successfully implemented an integrative curriculum model. The results of the study show that the integration of Islamic values and global needs can be realized through various strategies, such as strengthening the curriculum based on classical Islamic texts (kitab kuning) by adding science and technology subjects, developing soft skills and hard skills based on sharia, and establishing partnerships with formal educational institutions and industries. With innovative and adaptive curriculum management, pesantren can produce graduates who not only possess a strong understanding of religion but are also able to compete on a global level